Etiological Factors and Visual Outcomes of Dense Vitreous Hemorrhage in Patients Aged 80 years and above over the Past Decade in a Tertiary General Hospital - Yuhua Ding; Bangtao Yao; Hui Ye; Fei Wang (Journal of Ophthalmology)
This study aimed to investigate the main etiological factors and visual outcomes in patients with dense vitreous hemorrhage (DVH) aged ≥80 years. We retrospectively included patients with DVH aged ≥80 years who were admitted to our ophthalmology department between January 1, 2010, and December 31, 2019. All patients underwent pars plana vitrectomy (PPV). Data regarding demographic characteristics; preoperative and postoperative best-corrected visual acuity (BCVA), intraocular pressure (IOP), and ophthalmic B-scan ultrasonography findings; intraoperative conditions; and postoperative complications were collected and analyzed. A total of 44 patients (44 eyes) were enrolled, with a median age of 82 years; among them, 25 patients (56.82%) were men. The median preoperative BCVA was 2.3 (1.1–3.0). The main etiological factors included retinal vein occlusion (RVO) (20 eyes, 45.45%), polypoidal choroidal vasculopathy (PCV) (15 eyes, 34.09%), proliferative diabetic retinopathy (PDR) (7 eyes, 15.90%), retinal arterial macroaneurysm (RAM) (1 eye, 2.27%), and posterior vitreous detachment (PVD) (1 eye, 2.27%). The median final BCVA was 1.92 (0.5–2.6). There was a significant postoperative improvement in the BCVA; moreover, branch RVO (BRVO) had a better postoperative visual prognosis than central RVO (CRVO), PCV, and PDR (P < 0.05). The final postoperative BCVA was significantly better when the initial BCVA was above hand motion (HM) than when it was HM or lower (P < 0.05). Our findings indicate that RVO, PCV, and PDR were the main causes of DVH. Microinvasive PPV is a safe and effective method that can clarify diagnosis and improve BCVA. Patients with BRVO and preoperative BCVA > HM may have a relatively good visual prognosis. For patients aged ≥80 years who have an appropriate general condition, PPV can be timely performed to treat DVH.